Usulan Peningkatan Kualitas Produk Pupuk NPK Reaksi 15-15-15 dengan Menggunakan Metode Six Sigma (Studi Kasus: PT Petrokimia Gresik) - Abizar Rahman Hadi; Dzakiyah Widyaningrum (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Product quality is an important factor in the fertilizer industry because it determines quality conformity and the effectiveness of use in the agricultural sector. This study aims to measure the defect rate of NPK reaction fertilizer 15-15-15, determine the Defects Per Million Opportunities (DPMO) value and sigma level, identify the main causes of defects, and formulate quality improvement proposals at the NPK Reaction 2 Plant of PT Petrokimia Gresik. The approach used in this study is Six Sigma with the DMAIC stages, consisting of define, measure, analyze, improve, and control. The research data consist of production data and defective product data collected over 30 days of observation with four Critical to Quality (CTQ) characteristics, namely NPK content, granule size, granule hardness, and moisture content. The data processing results show a total production of 15,795 tons with total defects of 579 tons. The DPO value of 0.009164 resulted in a DPMO of 9,164.29 and a sigma level of 3.86. Pareto analysis shows two dominant defects, namely nonconforming NPK content at 40.59% and non-uniform granule size at 30.92%. The p-control chart shows that all observation points are within the control limits, but defects continue to occur repeatedly. The proposed improvements focus on raw material control, feeder calibration, adjustment of reaction and granulation parameters, screen inspection, control of recycled material, drying stabilization, and periodic CTQ monitoring.